Structure of the 'open' form of Aspergillus nidulans 3-dehydroquinate synthase at 1.7 A resolution from crystals grown following enzyme turnover. - Nichols, C; Hawkins, A; Stammers, D (2004)
Crystallization of Aspergillus nidulans 3-dehydroquinate synthase (DHQS), following turnover of the enzyme by addition of the substrate DAHP, gave a new crystal form (form J). Although the crystals have dimensions of only 50 x 20 x 5 micro m, they are well ordered, diffracting to 1.7 A. The space group is C222(1), with unit-cell parameters a = 90.0, b = 103.7, c = 177.4 A. Structure determination and refinement to R = 0.19 (R(free) = 0.25) shows the DHQS is in the 'open' form with the substrate site unoccupied but with some loop regions perturbed. Previous crystals of open-form DHQS only diffracted to 2.5 A resolution. The use of enzyme turnover may be applicable in other systems in attempts to improve crystal quality.